2021
DOI: 10.1111/1468-4446.12828
|View full text |Cite
|
Sign up to set email alerts
|

Damaged hardmen: Organized crime and the half‐life of deindustrialization

Abstract: Despite frequent associations, deindustrialization features rarely in studies of organized crime, and organized crime is at best a spectral presence in studies of deindustrialization. By developing an original application of Linkon's concept of the “half‐life,” we present an empirical case for the symbiotic relationship between former sites of industry and the emergence of criminal markets. Based on a detailed case‐study in the west of Scotland, an area long associated with both industry and crime, the paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…While those subject to community supervision in Scotland remain under the purview of statutory social work services, often these services are under-resourced and over-stretched, with individual practitioners lacking any meaningful powers to address the socio-structural and systemic issues faced by their service users (Weaver et al, 2021). We therefore suggest that while many of our participants strive for the full citizenship enjoyed by those with ‘conventional’ lives, they are encumbered by a criminal justice system which imposes and exacerbates stigma (in the form of a criminal record), while doing little to address harms engendered by structural issues such discrimination, an absence of secure and stable employment opportunities, and the ongoing violence of deindustrialisation which is felt by many Scottish communities (Fraser and Clark, 2021).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While those subject to community supervision in Scotland remain under the purview of statutory social work services, often these services are under-resourced and over-stretched, with individual practitioners lacking any meaningful powers to address the socio-structural and systemic issues faced by their service users (Weaver et al, 2021). We therefore suggest that while many of our participants strive for the full citizenship enjoyed by those with ‘conventional’ lives, they are encumbered by a criminal justice system which imposes and exacerbates stigma (in the form of a criminal record), while doing little to address harms engendered by structural issues such discrimination, an absence of secure and stable employment opportunities, and the ongoing violence of deindustrialisation which is felt by many Scottish communities (Fraser and Clark, 2021).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…behaviour, personal identity) and social integration (e.g. social identity, social recognition, and a sense of belonging) (Power and Nolan, 2017; Weaver, 2015). Nonetheless, research has revealed a complex and contingent relationship between (un)employment, offending and desistance.…”
Section: Research Contextmentioning
confidence: 99%
“…Deindustrialisation has played a significant role in Scottish society since its effects were first felt in the latter part of the twentieth century. Throughout the 1980s in particular, the west of Scotland’s experience of industrial decline was more brutal than most other areas of Britain (Fraser & Clark, 2021), which Phillips attributes to a failure of government policy in managing manufacturing closures. Between 1960 and 1975, 10,000 Scottish men were losing manufacturing jobs every year, and this doubled to 20,000 between 1979 and 1987 (Knox, 1999, p. 110).…”
Section: Deindustrialisation In Scotland and Tunbrookementioning
confidence: 99%
“…В 2000-е гг. она оттесняется идеями деиндустриализации, в связи с чем анализируются положительные примеры её осуществления [39] и противоречия: сокращение рабочих мест [26], миграция, рост преступности [28], разрушение инфраструктуры [38], несоответствие индустриального образа современной реальности [31]. В итоге ряд авторов приходит к выводу, что промышленные города не обязательно отстают от непромышленных [24], признаётся важность государственных инвестиций в их развитие [23] и частной сторон [30].…”
Section: промышленный город и его акторы в поле научного исследованияunclassified